The development of modern biocenotic control methods for the ecological state of aquatic ecosystems of rivers - Удод, Вера Михайловна; Вильдман, Игрорь Лазаревич; Жукова, Елена Григорьевна (Eastern-European Journal of Enterprise Technologies, 2014)
Existing ecological-hygiene control methods for the AE state under the action of anthropogenic factors do not fully characterize the structural-functional changes in water bodies, and therefore do not characterize the degree of their transformation. Sanitary-hygienic standards (TLV, MPD) allow to determine the class of water pollution and changes in chemical composition. At the same time, in the process of self-purification of the water body, there is destruction of pollutants, which leads to the formation of new chemical compounds, which are not considered by the applied control methods. Therefore, for the characterization of biological regulation of aquatic ecosystems, it is advisable to use integrated environmental approaches, including the existing sanitary-hygienic standards and biocenotic methods were proposed. Biocenotic methods allow to determine ecotoxicokinetic processes in bio- and aquatic ecosystems and based on the analysis of the data obtained find out the cause-effect relations of AE, which lead to the transformation of AE.